Alternativas nutricionais para frangos de corte submetidos ao estresse por calor - Diogo de Moraes Cardoso (2013)
Two experiments were conducted to evaluate the effects of diet processing and diet nutrient levels on performance, carcass yield, economic viability, digestibility and physiological parameters of animals under two raising environment conditions. Seven hundred and twenty Ross ® male broilers where employed from which 360 were submitted to thermoneutral environment (experiment I) and 360 were submitted to heat stress (experiment II). The treatments consisted in physical form of feed (mash and pellet) and nutritional level (normal and dense) in completely randomized experimental design in a factorial 2 x 2 in 6 replications of 15 poultry each. The animals submitted to the thermoneutral environment showed both lower feed intake and weight gain when fed mash feed diets formulated with normal levels. On other performance variables there was no change. Under heat environmental stress, the animals consumed more feed when it was offered in the pelletized form. Feed conversion was only influenced by the nutritional level, increasing with feed density. Both experiments exerted no influence on Carcass yield and cuts. There was a larger accumulation of abdominal fat (P 0.05) in animals fed pelletized feed in thermoneutral environment. Regardless the environment the animals showed better economic efficiency rate when fed pelletized diets. However, the lowest production cost was observed by mash feed. The digestibility of dry matter and of crude protein was only affected by feed processing, and rose by pelletized feed under thermoneutrality. Under environmental heat stress the same was true only for crude protein. Caloric increase, rectal temperature and respiratory rate were higher in animals submitted to heat stress. Pelletized feed was decisive on broiler performance in thermoneutral environment. By cyclical heat stress the alternative which provided the best feed conversion value was nutritional density. Pelletizing and nutritional density increased production costs.